Prevalence and characterization of brucellosis and tuberculosis in cattle and its zoonotic risk associated factors in Rwanda - Van Heerden, Henriette (University of Pretoria, 2024)
Thesis (PhD (Veterinary Sciences))--University of Pretoria, 2021.